A three dimensional coupled VOF and Level set (VOSET) method with and without phase change on general curvilinear grids. (21st September 2020) - Cao, Zhizhu; Zhou, Jie; Liu, An; Sun, Dongliang; Yu, Bo; Wei, Jinjia
Highlights: A 3D VOSET method on general curvilinear grids is proposed for two-phase flow. An iterative geometric operation is introduced to calculate the level set function. The level set based continuum surface tension model on curvilinear grids is derived. The method has excellent performance in dealing 3D interface flow in complex domain. Abstract: A 3D coupled VOF and LS method (VOSET) on general curvilinear grids is developed for two-phase flow simulations in complex domains. The evolution of volume fraction with time is updated by calculating fluid volume fraction flux polyhedron passing through each face with geometrical approaches. The level set function is obtained by an iterative geometric operation. The level set based continuum surface tension model is derived to compute surface tension. Subsequently the model and the proposed coupled interfacial tracking method are incorporated into IDEAL, an incompressible Navier-Stokes solver. Finally, several benchmark problems including static bubble, sphere deformation, 3D Taylor instability growth, single bubble rising, two bubble merge and microchannel flow boiling are tested on irregular regions to validate the accuracy and robustness of the proposed method. The results show good agreement with previous literature results, indicating the present method is able to accurately simulate incompressible 3D two-phase flows in complex domains.